2013
DOI: 10.1371/journal.pone.0081945
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Suppression of STAT3 and GSK3β Is Involved in Growth Inhibition of Non-Small Cell Lung Cancer by Xanthatin

Abstract: Xanthatin, a sesquiterpene lactone purified from Xanthium strumarium L., possesses prominent anticancer activity. We found that disruption of GSK3β activity was essential for xanthatin to exert its anticancer properties in non-small cell lung cancer (NSCLC), concurrent with preferable suppression of constitutive activation of STAT3. Interestingly, inactivation of the two signals are two mutually exclusive events in xanthatin-induced cell death. Moreover, we surprisingly found that exposure of xanthatin failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…This suggests that these NSCLC cells have become dependent on the GSK3 pathway for proliferation during tumourigenesis. Consistent with the role of GSK3 in supporting a tumour phenotype, its inhibition has been shown to promote apoptosis in NSCLC cell lines [43] , [44] . By contrast we found that proliferation of another NSCLC cell line, A549 was insensitive to GSK3 inhibition.…”
Section: Discussionsupporting
confidence: 53%
“…This suggests that these NSCLC cells have become dependent on the GSK3 pathway for proliferation during tumourigenesis. Consistent with the role of GSK3 in supporting a tumour phenotype, its inhibition has been shown to promote apoptosis in NSCLC cell lines [43] , [44] . By contrast we found that proliferation of another NSCLC cell line, A549 was insensitive to GSK3 inhibition.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies showed that xanthatin had an antitumour effect in several tumour cells, including A549 nonsmall cell lung cancer cells, H1299 nonsmall cell lung cancer cells, B16‐F10 murine melanoma cells, human breast cancer MDA‐MB‐231 cells, HL‐60 cells, the human leukemic mast cell line LAD2, and Chinese hamster ovary cells (Li et al, ; Sanchez‐Lamar et al, ; Takeda, Nishimura, et al, ; Takeda, Noguchi, et al, ; Tao et al, ; Tao et al, ; Tao et al, ; Vera et al, ; Yu et al, ; L. Zhang, Ruan, et al, ). Here, we found that xanthatin significantly inhibited tumour growth in both nude mouse xenograft glioma and rat orthotopic implanted glioma in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The disordered intracellular JAK2/STAT3 signaling pathway is frequent in many carcinomas and is related to malignant features; therefore, blocking of this pathway can help decrease tumor burden and to improve chemosensitivity. The inhibition of GSK-3β is crucial for xanthation to exert its anticancer properties in NSCLC, and the restraint of inherent activation of STAT3 enhances this function [ 42 ]. C14orf166 has been found to participate in the development of cervical cancer, which is thought to be involved in the abnormal JAK2/STAT3 pathway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%